Role of microRNAs in premature ovarian insufficiency - Ying Guo; Junyan Sun; Dongmei Lai (BMC, 2017)
Abstract Premature ovarian insufficiency (POI) is a typical disorder of amenorrhea lasting for a minimum of 4 months. The typical characteristics comprised of declined estrogen and raised serum concentrations of follicle-stimulating hormone (FSH) in women <40-year-old, primarily originating from iatrogenic factors, karyotypic abnormalities, and genetic factors. However, the etiology of POI remains unknown in approximately 90% of cases. POI could lead to infertility, osteoporosis, cardiovascular disorder, and cognitive dysfunction. MicroRNAs (miRNAs) are a class of endogenous noncoding RNAs (ncRNAs) that can mediate post-translational silencing of the genes involved in the regulation of proliferation, differentiation, apoptosis, development, tumorigenesis, and hematopoiesis. Recently, the regulatory functions of miRNAs in the development of POI have been the topic of intensive research. The present review addresses the association of miRNAs' machinery genes (Dicer, Drosha, and XPO5) with POI and the miRNA expression profiles in the plasma of patients with POI. In addition, several specific miRNAs (miR-23a, miR-27a, miR-22-3p, miR-146a, miR-196a, miR-290-295, miR-423, and miR-608) related to POI are also examined in order to highlight the issues that deserve further investigation. A thorough understanding of the exact regulatory roles of miRNAs is imperative to gain novel insights into the etiology of idiopathic POI and offer new research directions in the field.